Brook Napier, D. (ed.) (2014): Qualities of Education in a Globalised World. Róterdam: Sense Publishers. 206 pp. ISBN: 978-94-6209-648-6 (paperback) - Lorente Rodríguez, Míriam (Journal of Supranational Policies of Education (JOSPOE), 2016)
Journal of Supranational Policies of Education (JoSPoE)